A zif-8 / pda composite material and a preparation method and application thereof

CN122643467APending Publication Date: 2026-08-28NORTHEAST AGRICULTURAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611150957.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-08-28

AI Technical Summary

Technical Problem

[0003]对于部分天然活性分子及抗肿瘤性药物存在水溶性差或稳定性差等问题,不能满足临床应用需求

Benefits of technology

本发明提供的ZIF-8@PDA,在负载及递送姜黄素方面具有良好的可行性。本发明通过聚多巴胺(PDA)对ZIF-8材料进行改性,提高了ZIF-8材料作为载体对药物的负载效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122643467A_ABST
    Figure CN122643467A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of drug delivery, in particular to a ZIF-8 / PDA composite material and a preparation method and application thereof. The ZIF-8 / PDA composite material provided by the application has good feasibility in terms of loading and delivering curcumin. The ZIF-8 material is modified by polydopamine, and the loading effect of the ZIF-8 material as a carrier on drugs is improved. The characterization results show that the drug loading performance of ZIF-8@PDA is obviously improved. The in-vitro release experiment results show that CuR@ZIF-8@PDA has more significant pH response drug release characteristics, shows good inhibition on Staphylococcus aureus and Escherichia coli, the hemolysis rate is 3.1%, is within a safe range, the inhibition on HepG2 cells is stronger than that of CuR@ZIF-8, and more obvious oxidative stress reaction and cell apoptosis can be induced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of drug delivery technology, and in particular to a ZIF-8 / PDA composite material, its preparation method, and its application. Background Technology

[0002] With the continuous development of modern medicine and drug therapy technologies, the role of drugs in prevention and treatment is becoming increasingly prominent. However, traditional drug delivery methods have many limitations in practical applications, such as low drug utilization, poor targeting, and difficulty in maintaining effective concentrations at the lesion site. Therefore, the development of safe and controllable drug delivery systems (DDS) has become one of the most popular research directions. Drug delivery systems based on functionalized nanoplatforms have already attracted widespread attention in the field of tumor therapy. Zeolitic imidazolate framework-8 (ZIF-8) has shown great potential in the construction of drug delivery carriers for tumor therapy due to its good structural tunability, thermal stability, chemical stability, and pH response characteristics.

[0003] Some natural active molecules and antitumor drugs suffer from poor water solubility or instability, which prevents them from meeting the needs of clinical applications. For example, curcumin (Cucumin, CuR), a natural polyphenol compound, has excellent biological activities such as antioxidation, anti-inflammation, antibacterial and antitumor effects. However, due to its strong hydrophobicity, poor chemical stability and rapid metabolism in vivo, its bioavailability is low, and it is difficult to achieve targeted therapy, thus limiting the full realization of its efficacy.

[0004] Furthermore, in vivo studies have shown that varying degrees of damage within the human body can lead to differences in pH, temperature, enzyme type, or enzyme quantity in the damaged tissue. In regenerative medicine research, rationally controlling the effective load of drugs helps reduce the risk of adverse reactions and improve therapeutic efficacy. By regulating external stimuli or specific chemical signals, the release rate and rhythm of active ingredients can be dynamically adjusted to achieve "on-demand release."

[0005] Therefore, developing an endogenous stimulus-responsive material that can be used as a drug delivery material for curcumin is of great significance for the clinical application of curcumin. Summary of the Invention

[0006] In view of this, the present invention provides a ZIF-8 / PDA composite material (ZIF-8@PDA), its preparation method and application. The ZIF-8 / PDA composite material provided by the present invention can effectively load and release curcumin.

[0007] The present invention provides a ZIF-8 / PDA composite material, comprising ZIF-8 material and polydopamine coated on the surface of the ZIF-8 material.

[0008] Preferably, the preparation method of the ZIF-8 material includes the following steps: mixing zinc nitrate and a portion of methanol to obtain a zinc salt solution, then mixing 2-methylimidazole and the remaining methanol to obtain a 2-methylimidazole solution, subsequently adding the 2-methylimidazole solution dropwise to the zinc salt solution while stirring, and then carrying out a coordination polymerization reaction; the mass ratio of zinc nitrate to a portion of methanol is 1.6:23~24; the mass ratio of zinc nitrate to 2-methylimidazole is 1.6:2.6~2.7.

[0009] Preferably, the coordination polymerization reaction is carried out at a temperature of 155-165 degrees Celsius and the holding time is 17-19 hours.

[0010] This invention also provides a method for preparing the ZIF-8 / PDA composite material described above, comprising the following steps: (1) Mix ZIF-8 material, methanol and water to obtain ZIF-8 dispersion; (2) The ZIF-8 dispersion is mixed with polydopamine and alkaline solution to react and obtain the ZIF-8 / PDA composite material.

[0011] Preferably, in step (1), the mixing is ultrasonic mixing; the power of the ultrasonic mixing is 220~260 W, the frequency is 35~45 kHz, and the time is 25~35 minutes.

[0012] Preferably, the concentration of the alkaline solution is 0.08~0.11 mol / L; the mass-to-volume ratio of the ZIF-8 material to the alkaline solution is (290~310) mg:3 mL.

[0013] Preferably, the mass ratio of the ZIF-8 material to polydopamine is 9~11:1.

[0014] Preferably, the reaction time is 2.8 to 3.2 hours.

[0015] The present invention also provides the application of the ZIF-8 / PDA composite material described above in the field of drug delivery.

[0016] Compared with the prior art, the present invention has achieved the following beneficial effects: The ZIF-8@PDA provided by this invention demonstrates good feasibility in loading and delivering curcumin. This invention improves the drug loading capacity of ZIF-8 material by modifying it with polydopamine (PDA).

[0017] This invention first prepared ZIF-8 material using a solvothermal method. Structural characterization results showed that ZIF-8 material had a dodecahedral morphology with a particle size of 700-800 nm. ZIF-8 material exhibited good CuR loading capacity, with a maximum drug loading rate of 36.34%. In vitro release experiments showed that CuR@ZIF-8 possessed pH-responsive drug release characteristics, with cumulative release rates of 83.01% and 90.75% after 24 h at pH 7.4 and pH 5.0, respectively. Furthermore, CuR@ZIF-8 showed inhibitory effects against both Staphylococcus aureus and Escherichia coli, with minimum inhibitory concentrations (MICs) of 150.00 μg / mL and 350.00 μg / mL, respectively. Biocompatibility results showed that the hemolysis rate of ZIF-8 material was only 2.3%, and it exhibited good biocompatibility in both C2C12 and HepG2 cells. Cell experiments further confirmed that CuR@ZIF-8 has a more significant inhibitory effect on HepG2 liver cancer cells and can induce apoptosis and oxidative stress damage to exert anti-tumor effects.

[0018] Following this invention, ZIF-8@PDA was prepared using a one-pot method. Material characterization results showed that ZIF-8@PDA successfully achieved surface modification of PDA while retaining the dodecahedral structure of ZIF-8 material, and its drug loading capacity was significantly improved, with a CuR drug loading rate of 51.72%, approximately 1.4 times that of pure ZIF-8 material. In vitro release experiments showed that CuR@ZIF-8@PDA exhibited more significant pH-responsive drug release characteristics, with cumulative release rates of 50.10% and 82.17% after 36 h at pH 7.4 and pH 5.0, respectively. Furthermore, CuR@ZIF-8@PDA showed good inhibitory effects against Staphylococcus aureus and Escherichia coli, with MICs of 93.75 μg / mL and 312.50 μg / mL, respectively. Biocompatibility results showed that the hemolysis rate of ZIF-8@PDA was 3.1%, within the safe range. Cell experiments further confirmed that CuR@ZIF-8@PDA had a stronger inhibitory effect on HepG2 cells than CuR@ZIF-8, and could induce more significant oxidative stress response and apoptosis.

[0019] In summary, this invention uses ZIF-8 material as the core drug delivery carrier and constructs a drug delivery system that combines pH-responsive characteristics and biocompatibility by introducing PDA for composite modification. Attached Figure Description

[0020] To more clearly illustrate the technical solutions of this invention, the accompanying drawings used in the embodiments of this invention or in the prior art are briefly described below. For those skilled in the art, other drawings can be derived from the following drawings without creative effort, and all such drawings are within the protection scope of this invention.

[0021] Figure 1 SEM images of the ZIF-8 material prepared in Example 1; where (a) is the SEM image at 20 K, (b) is the SEM image at 30 K, (c) is the SEM image at 50 K, and (d) is the SEM image at 80 K. Figure 2 The EDS elemental distribution and energy spectrum of the ZIF-8 material prepared in Example 1 are shown; where (a) is the carbon elemental distribution, (b) is the zinc elemental distribution, (c) is the nitrogen elemental distribution, and (d) is the total EDS spectrum. Figure 3 The XRD diffraction pattern of the ZIF-8 material prepared in Example 1; Figure 4 The BET test results of the ZIF-8 material prepared in Example 1 are shown; where (a) is the N2 adsorption-desorption curve of the ZIF-8 material and (b) is the pore size distribution of the ZIF-8 material. Figure 5 Thermogravimetric and differential thermal curves of the ZIF-8 material prepared in Example 1 are shown. Figure 6 Infrared spectra of CuR, ZIF-8 material prepared in Example 1, and CuR@ZIF-8 prepared in Example 2; Figure 7 XPS spectra of the ZIF-8 material prepared in Example 1; where (a) is the full spectrum, (b) is the C 1s high-resolution spectrum, (c) is the N 1s high-resolution spectrum, and (d) is the Zn 2p high-resolution spectrum. Figure 8 Particle size and zeta potential analysis diagrams of CuR, ZIF-8 material prepared in Example 1 and CuR@ZIF-8 prepared in Example 2; wherein, (a) is the zeta potential of CuR, ZIF-8 material prepared in Example 1 and CuR@ZIF-8 prepared in Example 2, and (b) is the dynamic light scattering (DLS) particle size distribution curve of ZIF-8 material; Figure 9 The drug release curves of CuR@ZIF-8 under different pH conditions; Figure 10 The MIC results of CuR and CuR@ZIF-8 against Staphylococcus aureus; Figure 11 The inhibitory effects of CuR and CuR@ZIF-8 on Staphylococcus aureus at different drug concentrations were investigated. Figure 12 The MIC results of CuR and CuR@ZIF-8 against Escherichia coli; Figure 13The inhibitory effects of CuR and CuR@ZIF-8 on Escherichia coli at different drug concentrations were investigated. Figure 14 The cytotoxicity of ZIF-8 material is shown in (a), where (b) represents the blood compatibility of ZIF-8 material and (c) represents the activity of C2C12 and HepG2 cells at different concentrations of ZIF-8 material. Figure 15 The survival rates of C2C12 cells and HepG2 cells under different concentrations of CuR and CuR@ZIF-8 are shown in (a) and (b) respectively. Figure 16 AO / EB staining results of HepG2 cells in the control group, CuR group, ZIF-8 group and CuR@ZIF-8 group (scale bar is 50 µm). Figure 17 The changes in MDA and SOD values ​​of HepG2 cells after treatment with the control group, CuR group, ZIF-8 group, and CuR@ZIF-8 group are shown. Among them, (a) shows the changes in MDA values ​​of HepG2 cells after treatment with ZIF-8, CuR, and CuR@ZIF-8, and (b) shows the changes in SOD values ​​of HepG2 cells after treatment with ZIF-8, CuR, and CuR@ZIF-8. Figure 18 DCFH-DA staining fluorescence images of HepG2 cells after treatment with the control group, CuR group and CuR@ZIF-8 group (scale bar is 50 µm). Figure 19 The images are scanning electron microscope (SEM) images of ZIF-8@PDA at different magnifications; where (a) is the SEM image at 20 K magnification, (b) is the SEM image at 30 K magnification, (c) is the SEM image at 50 K magnification, and (d) is the SEM image at 80 K magnification. Figure 20 The following are the EDS elemental distribution and energy spectrum of ZIF-8@PDA; where (a) is the C element distribution, (b) is the N element distribution, (c) is the O element distribution, (d) is the Zn element distribution, and (e) is the total energy spectrum. Figure 21 XRD pattern of ZIF-8@PDA; Figure 22 The BET results for ZIF-8@PDA are shown in the figure; (a) is the N2 adsorption-desorption curve, and (b) is the pore size distribution diagram. Figure 23 Thermogravimetric analysis chart of ZIF-8@PDA; Figure 24 Infrared spectra of CuR, ZIF-8 materials, ZIF-8@PDA, CuR@ZIF-8, and CuR@ZIF-8@PDA; Figure 25 The XPS spectra of ZIF-8@PDA are shown below; (a) is the full spectrum, (b) is the C 1s high-resolution spectrum, (c) is the O 1s high-resolution spectrum, (d) is the N 1s high-resolution spectrum, and (e) is the Zn 2p high-resolution spectrum. Figure 26 The diagrams show the Zeta potential and particle size distribution of ZIF-8@PDA; where (a) is the Zeta potential diagram of ZIF-8@PDA and (b) is the particle size distribution diagram of ZIF-8@PDA. Figure 27 The drug release curves of CuR@ZIF-8@PDA in PBS at different pH values; Figure 28 The MIC and MBC tests of CuR@ZIF-8@PDA against Staphylococcus aureus were performed. Among them, (a) shows the MIC results of CuR@ZIF-8@PDA against Staphylococcus aureus, and (b) shows the colony growth after treatment with different drug concentrations. Figure 29 The MIC and MBC tests of CuR@ZIF-8@PDA against Escherichia coli were performed. Among them, (a) shows the MIC results of CuR@ZIF-8@PDA against Escherichia coli, and (b) shows the colony growth after treatment with different drug concentrations. Figure 30 The cytotoxicity of ZIF-8@PDA is shown in (a), where (b) is the blood compatibility of ZIF-8@PDA and (c) is the physiological activity of C2C12 cells and HepG2 cells at different concentrations of ZIF-8@PDA. Figure 31 The survival rates of C2C12 cells and HepG2 cells under different concentrations of CuR, CuR@ZIF-8, and CuR@ZIF-8@PDA are shown in (a) and (b) respectively. Figure 32 AO / EB plots after treatment of HepG2 cells in each group (scale bar is 50 µm). Figure 33The changes in MDA and SOD values ​​after CuR@ZIF-8@PDA treatment of HepG2 cells are shown; (a) shows the change in MDA value after CuR@ZIF-8@PDA treatment of HepG2 cells, and (b) shows the change in SOD value after CuR@ZIF-8@PDA treatment of HepG2 cells. Figure 34 The image shows the DCFH-DA staining fluorescence of HepG2 cells after CuR@ZIF-8@PDA treatment (scale bar is 50 µm). Detailed Implementation

[0022] The present invention provides a ZIF-8 / PDA composite material, comprising ZIF-8 material and polydopamine coated on the surface of the ZIF-8 material.

[0023] In this invention, the preparation method of the ZIF-8 material may include the following steps: mixing zinc nitrate and a portion of methanol to obtain a zinc salt solution, then mixing 2-methylimidazole and the remaining methanol to obtain a 2-methylimidazole solution, and then adding the 2-methylimidazole solution dropwise to the zinc salt solution while stirring and continuing to stir, followed by coordination polymerization reaction.

[0024] In this invention, the zinc nitrate can be zinc nitrate hexahydrate.

[0025] In this invention, the methanol can be anhydrous methanol; the volume ratio of the partial methanol to the total methanol can be 45-55%, specifically 50%.

[0026] In this invention, the mass ratio of zinc nitrate to a portion of methanol can be 1.6:23~24, specifically 1.6:23.75.

[0027] In this invention, the mass ratio of zinc nitrate to 2-methylimidazole can be 1.6:2.6~2.7, specifically 1.6:2.63.

[0028] In this invention, the stirring speed during the simultaneous stirring and dripping can be 250~350 rpm, specifically 300 rpm, and the dripping rate can be 55~65 drops / minute, specifically 60 drops / minute.

[0029] In this invention, the continued stirring time can be 5-10 minutes, specifically 8 minutes. This invention uses continued stirring to change the liquid from transparent to white.

[0030] In this invention, the temperature of the coordination polymerization reaction can be 155~165 degrees Celsius, specifically 160 degrees Celsius, and the holding time can be 17~19 hours, specifically 18 hours.

[0031] In this invention, the coordination polymerization reaction may further include post-treatment of the obtained product; the post-treatment may include sequentially discarding the supernatant, collecting the precipitate, centrifuging, washing, and drying; the centrifugation speed may be 8500~9500 rpm, specifically 9000 rpm, and the time may be 3~5 minutes, specifically 4 minutes; the washing reagent may be anhydrous methanol; the washing may be performed more than 3 times; the drying temperature may be 55~65 degrees Celsius, specifically 60 degrees Celsius, and the holding time may be 11~13 hours, specifically 12 hours.

[0032] This invention coats polydopamine onto the surface of ZIF-8 material to obtain ZIF-8@PDA, thus overcoming the problems of inorganic materials and CuR in terms of biocompatibility and solubility. Through this composite strategy, this invention successfully develops an intelligent drug delivery system with an "integrated" feature—low toxicity, high efficiency, and high drug loading capacity.

[0033] This invention also provides a method for preparing the ZIF-8 / PDA composite material described above, comprising the following steps: (1) Mix ZIF-8 material, methanol and water to obtain ZIF-8 dispersion; (2) The ZIF-8 dispersion is mixed with polydopamine and alkaline solution to react and obtain the ZIF-8 / PDA composite material.

[0034] This invention involves mixing ZIF-8 material, methanol, and water (referred to as the first mixture) to obtain a ZIF-8 dispersion. In this invention, the mass ratio of ZIF-8 material to water can be 0.3:85~95, specifically 0.3:87, 0.3:89, 0.3:91, or 0.3:93.

[0035] In this invention, the volume ratio of methanol to water can be 9~11:89~91, specifically 10:90.

[0036] In this invention, the first mixing can be ultrasonic mixing; the power of the ultrasonic mixing can be 220~260W, specifically 240W, the frequency can be 35~45 kHz, specifically 40 kHz, and the time can be 25~35 minutes, specifically 30 minutes.

[0037] After obtaining the ZIF-8 dispersion, the present invention mixes the ZIF-8 dispersion with polydopamine and an alkaline solution (denoted as the second mixture) and reacts them to obtain the ZIF-8 / PDA composite material. In the present invention, the alkaline solution can be a sodium hydroxide solution; the concentration of the alkaline solution can be 0.08~0.11 mol / L, specifically 1 mol / L.

[0038] In this invention, the second mixing may include the following steps: under stirring conditions, polydopamine and alkali solution are added sequentially to the ZIF-8 dispersion.

[0039] In this invention, the stirring conditions can be magnetic stirring; the stirring speed can be 300~500 rpm, specifically 400 rpm.

[0040] In this invention, the mass ratio of ZIF-8 material to polydopamine can be 9~11:1, specifically 10:1.

[0041] In this invention, the mass-to-volume ratio of the ZIF-8 material and the alkaline solution can be (290~310) mg:3 mL, specifically 300 mg:3 mL.

[0042] In this invention, the reaction time can be 2.8 to 3.2 hours, specifically 3 hours.

[0043] In this invention, the reaction may further include centrifuging and drying the resulting product sequentially; the centrifugation may use deionized water; the centrifugation may be performed three or more times; the drying temperature may be 75-85 degrees Celsius, specifically 80 degrees Celsius, and the holding time may be 11-13 hours, specifically 12 hours.

[0044] The present invention also provides the application of the ZIF-8 / PDA composite material described above in the field of drug delivery.

[0045] The ZIF-8 / PDA composite material provided by this invention can be used as a drug delivery material for targeted delivery of anti-tumor drugs, such as curcumin. It has advantages such as low toxicity, high efficiency and high drug loading capacity, and has broad application prospects.

[0046] To further illustrate the present invention, the technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings and embodiments.

[0047] Example 1: In this embodiment, ZIF-8 material was prepared using a hydrothermal method. The specific steps are as follows: 1.6 g of zinc nitrate hexahydrate was dissolved in 30 mL of anhydrous methanol to prepare solution A; 2.63 g of 2-methylimidazole was also dissolved in 30 mL of anhydrous methanol to prepare solution B; under magnetic stirring at 300 rpm, solution B was added dropwise to solution A at a rate of 60 drops / min, and stirred for 10 min, during which the solution changed from transparent to white; the solution was placed in a reaction vessel and heated at 160 °C for 18 h. After the reaction was completed, the supernatant was discarded, the precipitate was collected, centrifuged at 9000 rpm for 3 min, washed three times with anhydrous methanol, and dried at 60 °C for 12 h to obtain ZIF-8 material.

[0048] Example 2: In this embodiment, CuR@ZIF-8 was synthesized using the ZIF-8 material prepared in Example 1. The specific steps are as follows: 20 mg of ZIF-8 material was dissolved in 100 mL of anhydrous ethanol and stirred at 400 rpm for 8 min. After thorough mixing, 40 mg of CuR was added, and the mixture was shaken in a shaker at 27 °C and 160 rpm for 24 h. After 24 h, the mixture was centrifuged at 3000 rpm for 3 min to obtain CuR@ZIF-8. A series of CuR@ZIF-8 compounds were obtained by adjusting the mass ratio of ZIF-8 material to CuR to 2:1, 1:1, 1:3, or 1:4.

[0049] Example 3: The specific steps for preparing ZIF-8@PDA in this embodiment are as follows: 300 mg of ZIF-8 material was dispersed in 100 mL (10% by volume) of methanol solution and sonicated for 0.5 h at an ultrasonic power of 240 W and an ultrasonic frequency of 40 kHz. After the ZIF-8 material was evenly dispersed, the beaker was removed and 30 mg of PDA was added under magnetic stirring at 400 rpm. Then, 3 mL of NaOH (0.1 mol / L) was added and the reaction was carried out for 3 h. After the reaction was completed, the mixture was centrifuged three times with deionized water. After centrifugation, the mixture was dried in an oven at 80 ℃ for 12 h to obtain ZIF-8@PDA.

[0050] Example 4: In this embodiment, CuR@ZIF-8@PDA was prepared using the same method as in Example 2, except that the ZIF-8 material was replaced with the ZIF-8@PDA prepared in Example 3, resulting in a series of CuR@ZIF-8@PDA.

[0051] Test Example 1: The ZIF-8 material of Example 1 was characterized using the following methods and steps: 1) The samples were analyzed by field emission scanning electron microscopy (SEM) and elemental distribution using a GeminiSEM300 field emission scanning electron microscope from ZEISS GmbH, Germany; further combined with energy dispersive X-ray spectroscopy (EDS). 2) Fourier transform infrared spectroscopy (FT-IR) analysis of the samples was performed using a Perkin Elmer Spectrum Three Fourier transform infrared spectrometer. During the testing process, dried potassium bromide (KBr) was used as the background sample. Sample preparation was performed using a pellet method, with a sample-to-KBr ratio greater than 1:100. The testing range was 4000–400 cm⁻¹. -1 between; 3) Thermogravimetric analysis (TGA) was performed on the samples using a TGA / DSC3+ thermogravimetric analyzer from Mettler, Switzerland. All samples were tested under a nitrogen atmosphere, with the temperature increased from room temperature to 800 °C at a rate of 10 °C / min. 4) The samples were analyzed by X-ray diffraction (XRD) using a Rigaku SmartLab SE X-ray diffractometer from Japan. The diffraction angle was measured from 5 to 80°. A copper target was used as the diffraction target, and the scanning speed was 10° / min. 5) The specific surface area and pore size (BET) of the samples were determined using a 3Flex surface area and pore size analyzer from Micromeritics, USA. Before the test, each sample was degassed to remove moisture and adsorbed gases. The degassed temperature was 120 °C, and the degassed time was no less than 6 h. After degassed, under the same conditions, the amount of nitrogen adsorbed on the sample surface was measured and analyzed to calculate the specific surface area, pore size distribution, etc. of the samples. 6) The samples were characterized using a Zetasizer Lab nanoparticle size and Zeta potential analyzer from Malvern Instruments (UK). The Zeta potential was measured using a sample cell of model DTS1070, while the particle size was measured using a sample cell of model DTS0012.

[0052] 7) The sample was tested using a Thermo Scientific K-Alpha instrument from the United States; 8) Test Result Analysis: SEM analysis results of ZIF-8 material are as follows: Figure 1 As shown, according to Figure 1As can be seen, the ZIF-8 material particles exhibit a uniform dodecahedral morphology. Observations under low magnification (20 K, 30 K) show that the sample is uniformly distributed in the field of view, without aggregation, and the particle size is between 750 and 850 nm. No other products were observed within this field of view, indicating that particle formation during the reaction process is controllable, and the product purity and morphology are consistent. Further observation under high magnification (50 K, 80 K) reveals that the nanostructure of the ZIF-8 material has a clear outline, and the crystal surface is relatively smooth. Slight texture and undulations appear on some structural surfaces, which may be related to uneven local growth rates during crystal growth or changes in surface micromorphology caused by subsequent cleaning and drying processes. A few particles show slight truncated angles and minor size differences, but these do not change the overall dodecahedral morphology, indicating that the ZIF-8 material prepared in Example 1 has good crystallinity, regular morphology, and structural stability as a drug delivery material.

[0053] The EDS elemental distribution and energy dispersive spectrum of ZIF-8 material are as follows: Figure 2 As shown, according to Figure 2 As can be seen in (a) of the image, carbon is evenly distributed and has a relatively wide distribution in this field of view; similarly, according to Figure 2 (b) and Figure 2 As can be seen in (c), the spatial distribution of Zn and N is basically consistent with the particle region, and the overall distribution is relatively uniform, with no obvious local enrichment or component stratification. This indicates that the material components are uniformly distributed and the framework structure is well formed. Figure 2 As can be seen in (d) of the EDS total spectrum, characteristic peaks of C, N and Zn can be clearly observed. The content of C element is 71.15%, the content of N element is 19.87%, and the content of Zn element is 8.89%. The reason for the high content of C element may be that the ligand of ZIF-8 material is 2-methylimidazole. In addition, the carbon coating on the surface of the conductive adhesive will also have a certain influence on the C content in the energy spectrum.

[0054] The XRD diffraction pattern of ZIF-8 material is as follows: Figure 3 As shown, according to Figure 3It can be observed that the ZIF-8 material exhibits a series of characteristic peaks at low diffraction angles (2θ = 7~20°), which is the range in which typical characteristic peaks of ZIF-8 material exist, and the (011) and (112) crystal planes are marked in the spectrum. This result indicates that Example 1 successfully synthesized a ZIF-8 material with a typical topological framework. The characteristic peaks in the XRD spectrum are clearly positioned and have sharp peak shapes, and no obvious impurity peaks are observed, indicating that a large number of other crystalline phase impurities were not generated in the sample, and the material purity is relatively high. At the same time, each diffraction peak has a large peak intensity, indicating that the internal crystal arrangement of the sample is relatively ordered and the degree of crystallization is good. The common dodecahedral shape of ZIF-8 material is usually related to its good crystal order and preferred crystal plane growth, so this result can be mutually confirmed with the regular polyhedral morphology observed by SEM above.

[0055] The BET test results of ZIF-8 material are as follows: Figure 4 As shown, according to Figure 4 As shown in (a), a sharp and rapid adsorption occurred in the low relative pressure region (P / P0 < 0.1), which quickly stabilized, and the adsorption and desorption curves basically overlapped, with no obvious hysteresis loop. According to the classification of adsorption curves, the ZIF-8 material synthesized in Example 1 belongs to the type I isotherm curve, which is the characteristic adsorption behavior of microporous materials. The BET test results show that the total specific surface area within the pores of the ZIF-8 material is 983.528 m². 2 / g, total pore volume is 0.56977 cm³. 3 / g.

[0056] from Figure 4 Curve (b) shows a high characteristic peak in the 2 nm micropore region, indicating that the pore volume of the material is mainly contributed by micropores, confirming the micropore-dominated result in the isotherm. In the 2–50 nm mesopore region, the pore size distribution continuously decreases, indicating the presence of a certain amount of mesopores in the ZIF-8 material. Calculations using the BET method show that the average pore size of the ZIF-8 material is 5.3445 nm, falling within the mesopore range. This is a result of the combined effect of intrinsic micropores and interparticle mesopores. In summary... Figure 4 As shown in (a) and (b), the ZIF-8 material exhibits a well-developed pore structure with abundant internal pore surfaces, predominantly composed of micropores. These intrinsic micropores provide ample internal pore surface area and adsorption sites, significantly enhancing the adsorption and storage capacity for drug molecules. Simultaneously, the 5.3445 nm average mesoporous structure addresses the issue of high molecular diffusion resistance in purely microporous materials. Mesoporous channels shorten molecular diffusion paths and reduce mass transfer resistance, structurally facilitating drug adsorption and loading.

[0057] Thermogravimetric and differential thermal curves of ZIF-8 material are shown in the figure. Figure 5 As shown, according to Figure 5It can be seen that the TGA curve shows only a slight mass change when the temperature rises from room temperature to around 500℃. This is due to the evaporation of a small amount of water adsorbed on the particle surface, indicating that the ZIF-8 material is relatively stable below 500℃. Significant weight loss occurs in the ZIF-8 material between 550 and 650℃, with the most significant weight loss occurring between 590 and 630℃. The TGA curve is also steeper in this range, and the DTA curve shows a strong peak within this range. This indicates that a fundamental structural change occurs in the ZIF-8 material within this temperature range, possibly due to the cracking of organic ligands and the collapse of the coordination framework. In the high-temperature region of 650–800℃, the ZIF-8 material still exhibits relatively slow weight loss, retaining approximately 60% of its original weight at 800℃. This is because the ligand in the ZIF-8 material is Zn. 2+ It cannot decompose as the temperature increases.

[0058] ZIF-8 material and its infrared spectrum of CuR@ZIF-8 are shown below. Figure 6 As shown, according to Figure 6 It can be seen that the ZIF-8 material exhibits typical 2-methylimidazolium ligand vibrational characteristics: at 3130 cm⁻¹ -1 A stretching vibration peak of the imidazole ring =CH appears at 2920 cm⁻¹. -1 Corresponding to -CH3 stretching vibration; approximately 1580 cm -1 The characteristic peak of the C=N stretching vibration of the imidazole ring can be observed at 1500–900 cm⁻¹. -1 Within this range, the spectrum contains multiple sets of absorption peaks related to the imidazole ring skeletal vibration (such as CN, CC, etc.), and also in the low wavenumber region (approximately 500 cm⁻¹). -1 The presence of absorption signals related to Zn-N coordination bond vibrations near CuR (in the vicinity of the 3200-3500 cm⁻¹) indicates that the framework structure of the ZIF-8 material prepared in Example 1 was successfully formed and maintained with good integrity. -1 It typically exhibits a broad -OH absorption band within the range of 1600–1650 cm⁻¹. -1 Nearby, C=O / C=C stretching vibrations characteristic of conjugate systems are observed; furthermore, at 1500 cm⁻¹... -1 Nearby and 1270 cm -1 1030 cm -1 Absorption peaks of aromatic ring vibration and CO (or COC) vibration are visible at the fingerprint region. In contrast, CuR@ZIF-8 retains the main characteristic peaks of ZIF-8 material, and exhibits absorption peaks at 1600 cm⁻¹. -1The intensity and shape of the absorption peaks in the vicinity and fingerprint region changed, with slight peak position shifts or broadening, indicating that curcumin was successfully introduced and loaded into the ZIF-8 material. These changes may be related to the interaction between the drug molecule and the carrier. Notably, the characteristic peaks related to the ZIF-8 material framework remained clearly discernible in the CuR@ZIF-8 spectrum, with no obvious disappearance of framework peaks or new strong absorption bands, further demonstrating that the loading process did not disrupt the crystal framework structure of the ZIF-8 material, indicating that the material possesses good structural stability.

[0059] To test the surface chemical composition and elemental distribution of ZIF-8 materials, XPS analysis was performed in this test case. The results are as follows: Figure 7 As shown. According to Figure 7 In (a), characteristic peaks of C 1s, N 1s, and Zn 2p can be observed, indicating that the ZIF-8 material is mainly composed of C, N, and Zn elements. This result corresponds to previous test results. Figure 7 As shown in (b), C1s can be decomposed into three components, with the peak at 284.80 eV being the most intense and dominant peak. This is mainly attributed to the chemical states corresponding to the CC / CH vibrations in the ligand carbon skeleton and saturated carbon structures such as methyl groups. The peak at 286.40 eV corresponds to the carbon and N in the ligand, as well as to trace oxidation on the particle surface, further confirming the presence of the imidazole ring as a ligand. Figure 7 As shown in (c), both nitrogen chemical states coexist in the figure, indicating that the nitrogen environment on the material surface is not singular. Part of the nitrogen is in a relatively stable imidazole ring structure, while the other part may have undergone electronic structure shifts due to surface sites, local hydrogen bonding / adsorption, or differences in coordination environment. This also reflects that the ZIF-8 material surface possesses a certain number of potential active sites. Figure 7 In (d), two distinct characteristic peaks of Zn 2p can be observed, one at 1045.22 eV and the other at 1045.22 eV. 1 / 2 Zn 2p at 1022.32 eV 3 / 2 The two peaks are sharp and clearly split, with no obvious abnormal shoulder peaks or additional zinc chemical state signals, indicating that the zinc chemical environment in the material is relatively simple and the framework structure is relatively stable. This suggests that the Zn element in the ZIF-8 material mainly exists as Zn. 2+ The existence of this form may be related to the Zn-N bonding that is typical in MOF materials.

[0060] Particle size and zeta potential analysis of CuR, ZIF-8 material prepared in Example 1, and CuR@ZIF-8 prepared in Example 2 are as follows: Figure 8 As shown, according to Figure 8As shown in (a), there are certain differences in the Zeta potential among CuR, ZIF-8, and CuR@ZIF-8 materials. CuR exhibits a potential of -15.06 eV, displaying a strong negative charge characteristic, mainly due to the dissociation of phenolic hydroxyl groups in the CuR molecule, resulting in a large number of negative charges on the molecular surface. ZIF-8 exhibits a potential of +8.75 eV, displaying a positive charge characteristic, because the Zn in the MOF framework... 2+ After coordination with imidazole ligands, the uncoordinated Zn sites exposed on the ZIF-8 surface, along with the protonated imidazole groups, give the ZIF-8 material a positive charge in aqueous solution, allowing it to adsorb negatively charged CuR molecules via electrostatic interactions. When CuR is loaded onto the ZIF-8 surface, the particles exhibit an overall negative charge with a potential of -6.59 eV, indicating that CuR adsorption significantly alters the charge environment of the ZIF-8 surface. Furthermore, the absolute charge value of CuR@ZIF-8 is lower than that of the original ZIF-8 material, suggesting that CuR successfully loaded and neutralized some of the positive charge in the ZIF-8 material. This weakens the electrostatic repulsion of the system, prevents particle aggregation, and ultimately forms a stable CuR@ZIF-8 composite system.

[0061] according to Figure 8 As shown in (b), the size of the ZIF-8 material is mainly concentrated between 700 and 800 nm, with a peak value around 758 nm after Gaussian nonlinear fitting. The distribution range of the ZIF-8 material is between 400 and 1100 nm. The sample is dominated by medium-sized particles and exhibits a normal distribution, indicating that the ZIF-8 material has uniform size, good dispersibility, and no obvious large particle agglomeration.

[0062] Test Example 2: The biological performance of CuR@ZIF-8 prepared in Example 2 was tested, as follows: 1) In vitro load and release behavior testing: (1) Curcumin drug loading: This invention uses ultraviolet spectrophotometry to test the loading behavior of curcumin. After centrifugation in Example 2, the supernatant was taken and the ultraviolet wavelength of curcumin at 427 nm was measured. The drug concentration in the supernatant was calculated using a standard curve, and the encapsulation efficiency of the carrier for curcumin was calculated according to the following formulas 1 and 2. D LE ) and drug loading ( D LC The results are shown in Table 1: Formula 1; Formula 2; in, M 0This refers to the drug content within the drug delivery carrier (CuR@ZIF-8). M N The total mass of the drug delivery carrier. M C This indicates the quality of curcumin added.

[0063] (2) Curcumin drug release behavior: This invention uses the dialysis bag method to conduct in vitro release experiments of curcumin. The dialysis bag specifications are (molecular weight cutoff of 8 kDa). Before testing, the dialysis bag is pretreated by boiling to remove surface plasticizers. The specific operation method is as follows: the dialysis bag is placed in a 1:1 volume ratio of anhydrous ethanol and ultrapure water mixture and soaked for half an hour. After soaking, it is boiled at 90°C for 30 minutes. After that, the dialysis bag is rinsed with deionized water and then soaked in deionized water and stored at -4°C for later use.

[0064] Because curcumin has low solubility in human buffer solutions, 10% anhydrous ethanol was added to standard phosphate-buffered saline (PBS) solution to serve as the curcumin release medium. 10 mg of the drug-loaded carrier was weighed and placed in a pre-treated dialysis bag. 10 mL of the release medium was added to the dialysis bag, which was then sealed with a clip. The bag was placed in a wide-mouth beaker, and 80 mL of the release medium was added. The beaker was then sealed with plastic wrap and placed on a magnetic stirrer in the dark at 110 rpm to simulate the drug release behavior of CuR@ZIF-8 in a tumor environment (pH=5.0) and under normal physiological conditions (pH=7.4). The absorbance of the liquid in the beaker was measured at intervals, and the drug concentration in the beaker was calculated based on the absorbance. The drug release amount was then calculated using Equation 3. Formula 3; 2) Blood compatibility test: This invention uses sterile anticoagulated sheep blood for blood compatibility testing. 5 mL of blood was centrifuged at 3000 rpm at room temperature. After discarding the supernatant, the blood was repeatedly washed with 0.9% physiological saline until no red color remained. The blood was then diluted with PBS (pH 7.4) to prepare a 2% erythrocyte suspension. Three groups were set up: sample group (material sample + 2.5 mL 2% erythrocyte suspension + 2.5 mL PBS), negative control group (2.5 mL suspension + 2.5 mL PBS), and positive control group (2.5 mL suspension + 2.5 mL distilled water). After mixing, the mixture was incubated at 37 ℃ for 1 h, followed by centrifugation at 1500 rpm for 3 min at room temperature. The supernatant was collected, and the absorbance was measured to assess the degree of hemolysis. The hemolysis rate was calculated according to Equation 4. Equation 4; in, OD 样 It is a sample group OD value; OD 阴 It is the negative control group OD value; OD 阳 It is the positive control group OD value.

[0065] 3) Determination of the antibacterial properties of drug-loaded carriers: This invention tested the inhibitory effects of Gram-positive and Gram-negative bacteria on drug-loaded carriers. *Escherichia coli* (E. coli) was selected. Escherichia coli ) and Staphylococcus aureus ( Staphylococcus aureus For the test strain, the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of the drug-loaded carrier were determined using a two-fold serial dilution method.

[0066] 4) Cell viability assay: To investigate the good biocompatibility of single-carrier and drug-loaded carriers with cells, this invention used the CCK-8 assay to treat mouse myoblasts (C2C12 cells) and hepatocellular carcinoma cells (HepG2 cells), respectively. After treating cells with different material concentrations and culture times, the absorbance at 450 nm was measured and cell viability was calculated to evaluate the effect of the materials on cell activity. Cell activity was calculated according to Equation 5: Formula 5; 5) AO / EB cell staining experiment: After passage, HepG2 cells were seeded onto plates. After 24 h, the culture medium was aspirated, and the cells were washed 2-3 times with PBS buffer. The medium was then replaced with fresh DMEM containing the drug-loaded vector. After 24 h, the culture medium was aspirated, and the cells were washed 2-3 times with PBS. Acridine orange (AO) and ethidium bromide (EB) were then diluted according to the manufacturer's instructions and added to the culture medium. 1-2 mL of staining solution was added to each well, and the cells were stained in the dark for 5 min. After staining with PBS 2-3 times, the cells were observed immediately using a laser confocal microscope.

[0067] 6) MDA, SOD, and ROS determination experiments: After passage, HepG2 cells were seeded onto culture plates and cultured for 24 h. The original culture medium was then washed off, and cultured for another 24 h with culture medium containing different drug carriers. Subsequently, the drug carriers were washed off with fresh culture medium, and further processing and detection were performed according to the instructions of the malondialdehyde (MDA) and superoxide dismutase (SOD) kits.

[0068] Adjust the concentration of the HepG2 cell suspension to 10. 5Cells / mL were seeded in 30 mm glass culture dishes. After 24 h of culture, the drug carrier was added, and the cells were cultured for another 24 h. The cells were then washed with PBS to remove residual drug from the surface. Subsequently, the cells were stained in the dark according to the instructions for the 2',7'-dichlorodihydrofluorescein diacetate (DCFH-DA) probe. After staining, the cells were washed 2-3 times with PBS, stored in the dark, and observed and imaged using a laser confocal microscope to assess intracellular ROS levels.

[0069] 7) Test Result Analysis: Table 1. Drug loading rates of drug-loaded carriers prepared with different mass ratios of carriers and drugs in Example 2:

[0070] As shown in Table 1, under the same loading time, the mass ratio of carrier to drug affects the drug loading efficiency of the drug-loaded carrier, showing a trend of first increasing and then decreasing. When m(ZIF-8):m(CuR) is 1:2, the ZIF-8 material achieves the highest loading efficiency for curcumin at 36.34%. However, as the mass ratio increases further, the drug loading efficiency of the ZIF-8 material decreases, reaching only 24.35% when m(ZIF-8):m(CuR) is 1:4. Combined with the BET test results, when excessive curcumin is added, the pore sites of the particles tend to saturate, which may lead to drug aggregation and prevent adsorption by the carrier.

[0071] The drug release curves of CuR@ZIF-8 under different pH conditions are as follows: Figure 9 As shown, according to Figure 9 It can be seen that under simulated tumor microenvironment conditions, the cumulative release rate of the drug reached 75.78% within the first 4 hours; while under normal physiological conditions (pH=7.4), the cumulative release rate was 68.63% during the same period. Subsequently, both groups entered a relatively slow release phase, and by 24 hours, the cumulative release rate in the tumor environment rose to 90.75%, while it was 83.01% under pH 7.4 conditions. The pH sensitivity of the ZIF-8 material essentially originates from the coordination interaction between its metal nodes and organic linkers. In the methanol system used for synthesis, 2-methylimidazolium readily undergoes deprotonation, forming negatively charged imidazolium salts / imidazolium anions, which then interact with Zn via nitrogen atoms. 2+ Coordination forms a stable Zn-N bond network. Upon entering an acidic environment (pH=5.0), 2-methylimidazolium is easily reprotonated, reducing its coordination ability and thus weakening or even destroying the Zn-N coordination bonds, leading to the disintegration of the skeleton.

[0072] The MIC results of CuR and CuR@ZIF-8 against Staphylococcus aureus are as follows: Figure 10 As shown, according to Figure 10It can be seen that the minimum inhibitory concentration (MIC) of CuR and CuR@ZIF-8 against Staphylococcus aureus was determined using the two-fold dilution method. In this test example, the initial concentration of curcumin was set to 1500.00 µg / mL. In the fourth well of a 96-well plate, after rexazine staining, the color of the wells was dark, while in the fifth well, the color changed from dark to light red. At this point, the drug concentration in the fourth well was 2 times the initial concentration. 3 The corresponding concentration was 187.50 µg / mL, therefore 187.50 µg / mL was determined to be the minimum inhibitory concentration (MIC) of CuR. Similarly, the initial concentration of CuR@ZIF-8 was 1200.00 µg / mL, and the concentration after dilution was 2 times the initial concentration. 4 When the color changes from dark to light, the MIC of CuR@ZIF-8 is determined to be 150.00 µg / mL.

[0073] The inhibitory effects of CuR and CuR@ZIF-8 on Staphylococcus aureus at different drug concentrations are as follows: Figure 11 As shown, according to Figure 11 It can be seen that in the blank control case, Staphylococcus aureus grew vigorously. After adding an equal volume of drug with a concentration of MIC, the number of colonies decreased significantly. After adding an equal volume of drug with a concentration of 2MIC, no colony growth was observed. This indicates that 2MIC is the minimum bactericidal concentration (MBC) of the colony. Therefore, the minimum bactericidal concentration of curcumin is 375.00 µg / mL.

[0074] In CuR@ZIF-8, the MBC is 300.00 µg / mL. This is likely due to the Zn content in the ZIF-8 material. 2+ This is related to the shared contribution of CuR. ZIF-8 can release Zn in the system. 2+ Released Zn 2+ It can increase bacterial cell membrane permeability and cause K + Plasma leakage disrupts membrane integrity and inhibits bacterial growth.

[0075] The MIC results of CuR and CuR@ZIF-8 against Escherichia coli are as follows: Figure 12 As shown, according to Figure 12 It can be seen that the initial concentration of CuR was 3000.00 µg / mL, and the curcumin drug group was at 2 4 When the color changes from dark to red, it indicates that the drug concentration is 2. 3 At this point, the MIC of curcumin was 375.00 µg / mL. Similarly, the inhibitory concentration against E. coli after CuR@ZIF-8 treatment was also 375.00 µg / mL.

[0076] The inhibitory effects of CuR and CuR@ZIF-8 on Escherichia coli at different drug concentrations are as follows: Figure 13 As shown, according to Figure 13 As can be seen, at a concentration of 700.00 µg / mL, the colony count for both CuR and CuR@ZIF-8 was 0 CFU / g, therefore the MBC for both CuR and CuR@ZIF-8 against *E. coli* was 700.00 µg / mL. The inhibitory concentrations of both CuR and CuR@ZIF-8 against *Staphylococcus aureus* were better than those against *E. coli*. This may be because the cell membrane of Gram-negative bacteria consists of a thin peptidoglycan cell wall, further covered by an outer membrane containing lipopolysaccharide (LPS). The LPS permeability barrier significantly reduces the entry and accumulation of lipid-soluble / hydrophobic compounds; in contrast, Gram-positive bacteria lack this outer membrane structure. This makes *Staphylococcus aureus* more easily inhibited by the drug.

[0077] To assess the extent of ZIF-8 material's damage to erythrocytes, this test case used fresh mammalian blood for blood compatibility testing, and negative and positive controls were set up. The results are as follows: Figure 14 As shown in (a) of the diagram. According to Figure 14 As shown in (a), the hemolysis rate of the material is 2.3%, which is lower than the safety threshold of 5.0%. This indicates that the ZIF-8 material causes minimal damage to red blood cells, meeting the requirements for hemolysis experiments on biomaterials. This may be because the ZIF-8 material exhibits good particle dispersion under near-physiological conditions, preventing significant aggregation. Under physiological conditions, the ZIF-8 material is relatively stable and will not release excessive Zn over a certain period of time. 2+ This is insufficient to cause significant membrane damage. Furthermore, after entering the bloodstream, ZIF-8 materials can rapidly adsorb plasma proteins to form protein coronas. These protein coronas can passivate the particle surface and reduce their interaction with the cell membrane. Previous studies have shown that the protein coronas formed by plasma proteins can significantly inhibit nanoparticle-mediated erythrocyte hemolysis, thereby improving blood compatibility.

[0078] To evaluate the cytotoxicity of ZIF-8 material, this test case used the CCK-8 assay to detect its effects on the viability of mouse myoblasts (C2C12) and hepatocellular carcinoma cells (HepG2), respectively. The results are as follows: Figure 14 As shown in (b) of the diagram. According to Figure 14As shown in (b), when the concentration of ZIF-8 material was 10 µg / mL, the relative viability of both cell types was above 100%, which may be related to the mild promoting effect of low-dose material on cell metabolism or proliferation. This result indicates that ZIF-8 material has good cell compatibility and biocompatibility at lower concentrations. With increasing concentration, the cytotoxicity of ZIF-8 material gradually increased. At a concentration of 160 µg / mL, the viability of C2C12 cells was 74.2% and that of HepG2 cells was 78.18%, indicating that ZIF-8 material maintained good biocompatibility for both cell types at higher concentrations. The relative viability of HepG2 cells was slightly higher than that of C2C12 cells at all concentrations, which may be related to the faster proliferation rate and more active metabolic level of HepG2 cells as tumor cells, thus showing a higher response in the detection.

[0079] In cell viability assays, the survival rates of C2C12 and HepG2 cells at different concentrations of CuR and CuR@ZIF-8 were as follows: Figure 15 As shown, according to Figure 15 It can be seen that the effects of CuR and CuR@ZIF-8 on the viability of both cell types exhibit a concentration-dependent change. For C2C12 cells, when the drug concentration was 10 µg / mL, the cell viability remained in the range of 90-105%. As the drug concentration increased, cell viability gradually decreased. Finally, at 40 µg / mL, the survival rate of mouse myoblasts in the CuR@ZIF-8 group was 70.39%, which was not significantly different from the 70.74% in the pure CuR group. This indicates that the two treatments had relatively mild toxicity to C2C12 cells within this concentration range and had good biocompatibility. Compared with C2C12 cells, HepG2 cells were more sensitive to CuR@ZIF-8. With increasing drug concentration, the decrease in cell viability was more significant. At CuR@ZIF-8 drug concentrations of 20 µg / mL and 40 µg / mL, the survival rates of HepG2 cells were 60.52% and 41.32%, respectively, while the decrease in viability of free CuR was relatively smaller. The above results indicate that CuR@ZIF-8 cells maintain good biocompatibility with normal cells while also exhibiting better inhibitory effects on liver cancer cells. This may be because ZIF-8 material is more easily taken up by tumor cells than free CuR. Furthermore, ZIF-8 material is more prone to structural changes in the acidic / lysosomal environment within cells, potentially leading to more effective CuR release and thus enhancing the inhibitory effect on HepG2 cells.

[0080] AO / EB double staining is commonly used to assess apoptosis. AO can penetrate intact cell membranes, enter cells, and bind to DNA, emitting green fluorescence; while EB can only enter cells with damaged membranes, binding to nucleic acids and emitting red fluorescence. This test included a control group (no drug or carrier), a CuR group (with curcumin), a ZIF-8 group (with ZIF-8 material), and a CuR@ZIF-8 group (with CuR@ZIF-8). The AO / EB staining results of HepG2 cells in each group are shown below. Figure 16 As shown, according to Figure 16 It can be seen that the control group HepG2 cells mainly exhibited green fluorescence stained with AO, while the EB red fluorescence was weak, indicating that the cell membrane structure of the control group was intact and the cells had good viability. Compared with the control group, the CuR group showed significantly enhanced red fluorescence intensity, and some cells in the Merge group showed yellow / orange fluorescence, indicating that CuR can induce apoptosis. The CuR@ZIF-8 group showed the most significant red fluorescence, with a further increase in the proportion of yellow / orange cells and a significant decrease in green cells, indicating that the CuR@ZIF-8 drug delivery system caused stronger damage to HepG2 cells. The study by Xiao Mi et al. found that vector delivery may enhance intracellular uptake or promote the intracellular effect of drugs, thereby aggravating membrane damage and cell death.

[0081] MDA is a typical end product produced during lipid peroxidation. Changes in its content can serve as an indicator of intracellular lipid peroxidation levels, indirectly reflecting antioxidant defense capacity, the rate and intensity of lipid peroxidation, and the degree of oxidative damage to tissues. The changes in MDA values ​​in HepG2 cells after treatment with ZIF-8, CuR, and CuR@ZIF-8 are shown below. Figure 17 As shown in (a), according to Figure 17 As shown in (a), compared with the control group, the MDA value of cells treated with ZIF-8 material did not change significantly, indicating that ZIF-8 material did not cause oxidative damage to HepG2 cells. The CuR@ZIF-8 group had the highest MDA expression, and CuR@ZIF-8 significantly interfered with the mitochondrial respiratory chain complex and the activity of key enzymes in mitochondria, further aggravating the damage to the HepG2 cell membrane structure, ultimately inducing significant oxidative stress damage in the cells. SOD is a class of antioxidant defense enzymes, whose main function is to catalyze superoxide anion free radicals (O2• - A disproportionation reaction occurs, producing H2O2 and O2 (2O2• - +2H + →H2O2+O2), thereby eliminating one of the earliest and most common reactive oxygen species (ROS) produced in cells, maintaining redox homeostasis. Therefore, changes in SOD content can reflect changes in free radicals. SOD expression levels after treatment of HepG2 cells under different conditions are as follows: Figure 17As shown in (b) in the figure, according to Figure 17 As can be seen from (b), after treatment with ZIF-8 material, the intracellular SOD value did not change significantly. In the CuR@ZIF-8 group, the SOD expression level decreased the most compared with the control group. This also indicates that under this condition, free radicals in the cell cannot be completely eliminated, which ultimately leads to the disruption of intracellular redox homeostasis and cell damage.

[0082] DCFH-DA staining is commonly used to assess intracellular reactive oxygen species (ROS) levels. As one of the early apoptosis signals, ROS accumulation can promote the oxidation of non-fluorescent DCFH to green fluorescent DCF, thus enabling the visual detection of intracellular ROS. This test case uses the DCFH-DA probe to detect ROS expression levels in different groups of CuR and CuR@ZIF-8 cells. The results are as follows: Figure 18 As shown, according to Figure 18 As can be seen, compared with the control group, both the CuR and CuR@ZIF-8 groups showed obvious green fluorescence signals, indicating that CuR and CuR@ZIF-8 caused some damage to HepG2 cells. The stronger green fluorescence intensity in the CuR@ZIF-8 group compared with the CuR group indicates that CuR@ZIF-8 produced more ROS. This phenomenon may be related to the carrier promoting cellular uptake and the intracellular acidic environment triggering drug release, thereby enhancing mitochondrial-related oxidative damage.

[0083] Overall, this test example used SEM, XRD and other characterization methods to determine the microstructure, crystal structure and other properties of the prepared ZIF-8 material. The results show that the ZIF-8 material exhibits a dodecahedral shape with a particle size of approximately 700-800 nm.

[0084] In a pH-responsive drug delivery system using ZIF-8 material as a carrier and curcumin as a model drug, this invention employs an impregnation method to load curcumin onto ZIF-8 material. Results show that when the drug-to-carrier mass ratio is 2:1, ZIF-8 material exhibits the best loading effect for curcumin, achieving a drug loading capacity of 36.34%. Release experiments demonstrate that CuR@ZIF-8 achieves a cumulative release of over 90% within 24 hours in a tumor environment (pH=5.0).

[0085] In antibacterial experiments, the CuR@ZIF-8 drug delivery system demonstrated inhibitory effects against both Gram-positive and Gram-negative bacteria. The MIC and MBC against Staphylococcus aureus were 150.00 μg / mL and 300.00 μg / mL, respectively, while those against Escherichia coli were 350.00 μg / mL and 700.00 μg / mL, respectively. This is likely because the cell membrane of Gram-negative bacteria is composed of a thin peptidoglycan cell wall, thus preventing some drugs from entering the bacteria. Regarding biocompatibility, the hemolysis rate of the ZIF-8 material was 2.3%, below the 5% safety threshold, indicating that the ZIF-8 material has good biocompatibility.

[0086] In the cell experiments, this test case first tested the biosafety of the ZIF-8 material and then examined whether CuR and CuR@ZIF-8 inhibited the activity of HepG2 cells. In the cell viability assay, the CuR@ZIF-8 group showed the strongest interference with HepG2 cell activity at the same concentration. AO / EB assays indicated that CuR@ZIF-8 could induce apoptosis. MDA, SOD, and ROS assays showed that the CuR@ZIF-8 drug delivery system could cause oxidative stress damage in HepG2 cells.

[0087] In summary, this invention successfully constructed a drug delivery system with high loading capacity, pH responsiveness, and good biocompatibility, providing a new approach for nanomedicine delivery systems. However, although ZIF-8 materials possess certain drug loading and pH-responsive release capabilities, their surface active sites are limited, and there is still room for further improvement in drug-carrier interactions.

[0088] Test Example 3: The ZIF-8@PDA prepared in Example 3 was characterized. Unless otherwise specified, the test methods and instruments were the same as in Example 1. The test results are as follows: Scanning electron microscope images of ZIF-8@PDA at different magnifications are shown below. Figure 19 As shown, according to Figure 19 As can be seen, under low magnification, the ZIF-8@PDA prepared in Example 3 exhibits a uniform particle distribution in the field of view, with most particles concentrated between 750 and 900 nm. Compared to previously prepared ZIF-8 materials, the particle diameter of ZIF-8@PDA is increased, which is attributed to the coating layer formed by dopamine molecules on the surface of the ZIF-8 material. Figure 19As shown in (d), the surface of ZIF@PDA particles is rougher than that of ZIF-8 material. The originally smooth and flat crystal faces show obvious "wrinkles," and some edges are more rounded. These characteristics indicate that dopamine self-polymerizes under alkaline conditions and forms a continuous coating layer on the surface of ZIF-8 material. Furthermore, ZIF-8@PDA maintains its dodecahedral shape, and no particle structure collapse or aggregation was observed, suggesting that PDA had minimal impact on the structure of ZIF-8 material during the coating process. Considering both the increased particle diameter and the changes in surface morphology, it can be inferred that PDA successfully coated the surface of ZIF-8 material and formed a stable shell-core structure.

[0089] The EDS of ZIF-8@PDA provides the elemental distribution of C, N, O, and Zn, as well as the overall energy spectrum, such as... Figure 20 As shown, according to Figure 20 As can be seen, C, Zn, and N elements exhibit a continuous and uniform distribution across the field of view, without significant enrichment or deficiency. O element, while showing a relatively weak signal, still maintains a uniform distribution. Characteristic peaks for C, N, O, and Zn can be observed in the total energy spectrum, with the Zn peak being the most significant. Similar to ZIF-8, C has the highest mass percentage (51.01%) and Zn has the highest mass percentage (25.35%) in ZIF-8@PDA, while O is relatively low at 2.98%. This may be because PDA is formed by the oxidative self-polymerization of dopamine, and its structure still retains oxygen-containing groups such as catechol and quinone (=O).

[0090] The XRD pattern of ZIF-8@PDA is as follows: Figure 21 As shown, according to Figure 21 As can be seen from the XRD results, the characteristic peaks of ZIF-8@PDA are basically consistent with those of the single ZIF-8 material, and no new or impure peaks appear. This indicates that the introduction of PDA did not cause the collapse of the ZIF-8 material framework. This phenomenon may be due to the fact that the ZIF-8 material framework has a certain degree of stability, and its structure is more likely to dissociate under acidic conditions due to the protonation of Zn-N bonds. In Example 3, the addition of 0.1 mol / L NaOH maintained an alkaline environment, which was more conducive to maintaining the deprotonated state of 2-methylimidazole. In addition, the formation of PDA is due to the oxidative self-polymerization of dopamine under alkaline conditions, which can form hydrogen bonds and π–π interactions with the functional groups on the surface of ZIF-8 material to achieve deposition, thereby forming a relatively dense coating layer on the particle surface without significantly changing the ordered structure of the internal lattice. The lower peak intensity of ZIF-8@PDA compared to the unmodified form may be due to the absorption effect of the formed coating layer on X-rays.

[0091] The BET results for ZIF-8@PDA are as follows: Figure 22 As shown, according to Figure 22 In (a), it can be observed that the N2 adsorption-desorption isotherm of ZIF-8@PDA gradually increases and tends to stabilize when P / P0 < 0.4. As P / P0 increases, the adsorption curve and desorption curve show obvious separation and form a hysteresis loop, exhibiting the characteristics of a type IV isotherm. Figure 22 As shown in Figure (b), the average pore size of ZIF-8@PDA is 5.3445 nm. Combined with the adsorption-desorption curve results, micropores still dominate in ZIF-8@PDA. The specific surface area of ​​ZIF-8@PDA is 19.9271 m². 2 The specific surface area and pore volume of ZIF-8@PDA are lower than those of pure ZIF-8, which may be due to the PDA layer blocking the pore openings, partially occupying pores, and reduced pore accessibility caused by changes in particle packing after coating. Although the specific surface area and pore volume of ZIF-8@PDA are lower than those of pure ZIF-8, this does not necessarily mean that the drug loading capacity is weakened. On the contrary, the surface of the PDA coating layer is rich in active functional groups such as catechols and amines, which can form hydrogen bonds, π–π interactions, and electrostatic adsorption with drug molecules, thus providing more binding sites for drug molecules in addition to pore adsorption.

[0092] Thermogravimetric analysis chart of ZIF-8@PDA is as follows: Figure 23 As shown, the thermogravimetric curve of ZIF-8@PDA under N2 atmosphere can be divided into three main stages. According to... Figure 23 It can be seen that when the room temperature rises to 150℃, the TG curve shows a slight downward trend, with only slight weight loss, and the DTG curve approaches 0. This is attributed to the volatilization of water and residual methanol on the ZIF-8@PDA surface. Weight loss is slow in the 150~550℃ range, and no obvious peak appears in the DTG curve during this stage, indicating that the synthesized ZIF-8@PDA has good thermal stability in this range. When the temperature rises above 550℃, ZIF-8@PDA experiences significant weight loss, and the DTG curve reaches its peak at 614℃, with the peak position similar to that of pure ZI. The similarity to F-8 material indicates that PDA coating did not change the thermal decomposition behavior of the main ZIF-8 material framework. Therefore, this range is the main weight loss range of ZIF-8@PDA. This may be due to the breaking of Zn-N coordination bonds inside ZIF-8@PDA and the thermal decomposition and volatilization of 2-methylimidazolium ligands. In the range of 650~800℃, the weight loss rate of ZIF-8@PDA gradually slows down, and at 800℃, the particles still contain 64.22% of the remaining mass. This is due to the carbonization of organic components and the remaining Zn-related inorganic residues under nitrogen atmosphere.

[0093] Infrared spectra of CuR, ZIF-8 materials, ZIF-8@PDA, CuR@ZIF-8, and CuR@ZIF-8@PDA are shown below. Figure 24 As shown, according to Figure 24 As can be seen, the FT-IR results show that the ZIF-8 material at 1580 cm⁻¹... -1 The characteristic peaks appearing nearby are attributed to the stretching vibrations of C=N / C=C in the imidazole ring, 1140~1000 cm⁻¹ -1 The absorption peaks within the range correspond to CN stretching vibrations, while those at 420–500 cm⁻¹ correspond to CN stretching vibrations. -1 The nearby absorption peaks can be attributed to Zn-N coordination vibrations, and these characteristic peaks collectively demonstrate the successful construction of the ZIF-8 material's framework structure. After PDA modification, ZIF-8@PDA still retains the aforementioned characteristic peaks. Combined with SEM images, it can be concluded that PDA coating did not destroy the crystal framework of the ZIF-8 material. Meanwhile, in the 3200–3500 cm⁻¹ range... -1 A wider absorption band appears nearby, mainly due to the vibrational absorption of phenolic hydroxyl and amino groups in the PDA molecule, indicating that PDA has been successfully introduced into the ZIF-8 material surface. In CuR@ZIF-8@PDA, in addition to retaining the skeletal characteristic peaks of the ZIF-8 material, the 1500–1400 cm⁻¹ band is also present. -1 The superposition and enhancement of CuR-related absorption peaks within the region indicate that CuR has been successfully loaded into ZIF-8@PDA. The characteristic peaks of the ZIF-8 material remain after drug loading, suggesting that the drug loading process did not cause significant damage to the framework structure, and the ZIF-8 material maintains good structural integrity. Therefore, the FT-IR results confirm the successful construction of ZIF-8@PDA and the effective loading of CuR at the molecular structure level.

[0094] The XPS spectrum of ZIF-8@PDA is as follows: Figure 25 As shown, according to Figure 25 In (a), characteristic peaks of C 1s, N 1s, and Zn 2p, which are present in ZIF-8 materials, can be observed. Simultaneously, the characteristic peak of O 1s can also be observed. This characteristic peak mainly originates from oxygen-containing functional groups such as catechol-OH and quinone / carbonyl C=O in PDA. According to... Figure 25 As can be seen in (b), the main peak of C 1s is located at 284.8 eV, corresponding to the C / C=C bond. A smaller peak is also present to the left of the main peak at 287.68 eV. This is because dopamine needs to form polydopamine under oxidative conditions, leading to the peroxidation of C to form C=O. Similarly, in Figure 25 As can be seen in (c), the peak at 531.68 eV confirms the presence of C=O unsaturated bonds, while the peak at 533.98 eV is caused by O saturated bonds. Figure 25As can be seen from (d), N 1s can be divided into two nitrogen chemical states: the NC bond at 399.08 eV corresponds to a partial CN bond in the imidazole ring, and the C=N unsaturated bond at 401.18 eV. This indicates that multiple nitrogen chemical states exist in ZIF-8@PDA. Figure 25 As can be seen from (e), the Zn 2p spectrum shows a typical orbital double splitting peak, indicating that zinc in the sample is mainly in the form of Zn. 2+ The Zn 2p signal remains intact and is still clearly detectable. Compared with the Zn control peak of ZIF-8 material, the peak position is almost unchanged, indicating that the PDA coating did not cause a change in the Zn valence state, and the ZIF-8 material framework remains stable. Combined with XRD analysis, the PDA coating did not cause a change in the crystal phase of ZIF-8 material, indicating that the modification process mainly occurred on the surface of ZIF-8 material particles, and the ZIF-8 material framework structure was maintained. Combined with XPS full spectrum and high-resolution spectrum, it can be seen that C 1s, N 1s and Zn 2p signals related to the ZIF-8 material framework, as well as the O 1s signal introduced by PDA modification, were simultaneously detected on the ZIF-8@PDA surface. The peak separation results of C 1s and N 1s indicate that there are multiple chemical states on the ZIF-8@PDA surface corresponding to the aromatic carbon framework, CN bond and conjugated nitrogen-containing structure. While maintaining the bulk Zn of ZIF-8 material... 2+ Based on the node and ligand framework features, a PDA layer rich in oxygen-containing functional groups was successfully constructed on the ZIF-8@PDA surface, thereby achieving surface coating and functionalization of ZIF-8 materials.

[0095] The zeta potential and particle size distribution of ZIF-8@PDA are shown in the figure below. Figure 26 As shown, according to Figure 26 As shown in (a), ZIF-8@PDA exhibits a negative potential of -19.86 eV, while the initial potential of ZIF-8 material is +8.75 eV, exhibiting positive electrical properties. The decrease in particle potential after PDA modification may be due to the fact that phenolic hydroxyl / quinone groups on the PDA surface are more likely to become negatively charged under neutral or slightly alkaline conditions. After loading curcumin onto ZIF-8@PDA, the Zeta potential further decreases to -23.94 eV, indicating that the particle surface is more electronegative. The π–π stacking and hydrogen bonding between CuR and PDA alter the exposure of surface functional groups, making the Zeta potential more negative. Figure 26As shown in (b), the particle size distribution of ZIF-8@PDA exhibits a relatively obvious normal distribution after Gaussian curve fitting, indicating that the particle size distribution is relatively concentrated and the particle uniformity is good. The particle diameter is mainly concentrated in the 750~850 nm range, indicating that the PDA-modified ZIF-8@PDA maintains a relatively stable particle size range. Compared with pure ZIF-8 material, the average particle size of ZIF-8@PDA is increased. This is mainly attributed to the oxidative self-polymerization of dopamine under weakly alkaline conditions, which gradually deposits a PDA coating film on the surface of ZIF-8 particles, thereby increasing the particle outer diameter. The surface morphology changes observed by SEM corroborate the increase in particle size in the particle size test, indicating that PDA is not simply adsorbed onto the surface, but rather forms a coating layer of a certain thickness on the outer layer of the ZIF-8 material. Although the sample still mainly consists of particles in the 750–850 nm range, a small amount is still distributed in the higher particle size region. This indicates that some ZIF-8@PDA particles may have slightly agglomerated during the PDA polymerization coating process, or that the particle size distribution exhibits a certain degree of tailing due to the uneven thickness of the surface polymerization layer. This phenomenon is usually also manifested in SEM as tighter contact between local particles or slightly blurred boundaries. Overall, both particle size analysis and SEM results show that PDA has been successfully coated on the surface of ZIF-8 material, maintaining the original basic particle morphology while slightly increasing the particle size and making the surface rougher, thus providing favorable conditions for subsequent drug loading and interfacial interactions.

[0096] Test Example 4: The ZIF-8@PDA underwent bioperformance testing. Unless otherwise specified, the testing methods and equipment were the same as in Test Example 2. The test results are as follows: The loading characteristics of curcumin on ZIF-8@PDA are shown in Table 2.

[0097] Table 2. Drug loading rates of drug-loaded carriers prepared with different mass ratios of carriers and drugs in Example 4:

[0098] As shown in Table 2, the loading rate of curcumin on the carrier gradually decreased as the ratio of m(ZIF-8@PDA):m(CuR) decreased. The highest loading rate, exceeding 50% (51.72%), was observed at a ratio of 1:2. Subsequent ratios of 1:3 and 1:4 resulted in loading rates of 48.07% and 42.17%, respectively. Therefore, the optimal condition for loading CuR onto ZIF-8@PDA is a carrier-to-drug mass ratio of 1:2. Compared to pure ZIF-8 materials, ZIF-8@PDA exhibits improved drug loading capacity, primarily due to changes in the surface chemical environment and drug binding mechanism after PDA coating. PDA molecules contain abundant phenolic hydroxyl, amino, and aromatic structures, providing more adsorption sites for curcumin. Furthermore, the interaction between the drug and the carrier is enhanced through hydrogen bonding, π–π stacking, and van der Waals forces. The PDA coating layer also forms an additional drug-binding interface on the material surface, transforming the drug loading process from solely relying on the pore confinement effect of ZIF-8 materials to a synergistic "in-pore adsorption-surface binding" mechanism. Although the specific surface area of ​​the PDA-modified material may decrease, the increased number of surface active sites and enhanced interfacial interactions ultimately improve the overall drug loading capacity.

[0099] The drug release curves of CuR@ZIF-8@PDA in PBS at different pH values ​​are as follows: Figure 27 As shown, according to Figure 27 It can be seen that, under pH 7.4 conditions, the drug-loaded carrier released 27% of CuR in the first 4 hours, 45.89% after 12 hours, and then the drug release gradually leveled off. At 36 hours, 50.10% of the drug was released. Compared with ZIF-8 material, the release rate was lower, and the release time was extended from 24 hours to 36 hours. Under tumor conditions (pH=5.0), the total release of the drug-loaded carrier was 40.24% in the first 4 hours, 57.14% in 8 hours, and then the release gradually leveled off after 24 hours. At 36 hours, release ceased, with a total release of 82.17%.

[0100] Compared to ZIF-8 materials, ZIF-8@PDA exhibits stronger responsiveness under different pH conditions. The differences are mainly attributed to the acid sensitivity of the ZIF-8 material framework itself and the interfacial modulation effect of the PDA coating layer. ZIF-8 materials are composed of Zn... 2+ It forms through coordination with 2-methylimidazolium ligands, and its backbone is more susceptible to H under acidic conditions. +The attack causes the Zn-N coordination bonds to gradually weaken or even break, thereby promoting the loosening or partial degradation of the framework and accelerating drug release within the pores. The PDA layer is not a simple inert coating layer, but rather has a dual function of barrier and response regulation. The PDA layer can act as a "gatekeeper" to allow drug release under neutral conditions, while under acidic conditions, increased permeability triggers faster release. Therefore, the acid-responsive degradation of the ZIF-8 material framework and the gating regulation of the PDA layer together endow CuR@ZIF-8@PDA with a more significant pH-responsive release behavior.

[0101] The minimum inhibitory concentration (MIC) of CuR@ZIF-8@PDA against Staphylococcus aureus was determined using the two-fold dilution method. The results are as follows: Figure 28 As shown. According to Figure 28 It can be seen that, with an initial concentration of 1500.00 μg / mL, after staining with resazurin, the colonies were 2 5 The color changed from dark to light, therefore it was determined that the drug concentration was 2. 4 The minimum inhibitory concentration (MIC) of CuR@ZIF-8@PDA was 93.75 μg / mL. After treatment with the MIC concentration, the number of colonies decreased significantly, although a small number of colonies were still visible, indicating that CuR@ZIF-8@PDA had a significant inhibitory effect on colony growth at the administered concentration of 93.75 μg / mL. No colony growth was observed at the administered concentration of 2MIC; therefore, 187.50 μg / mL was determined to be the minimum bactericidal concentration (MBC) of CuR@ZIF-8@PDA against Staphylococcus aureus. This is mainly related to the regulation of surface interface properties by the PDA coating. PDA surface modification can significantly reduce the initial adhesion of bacteria to the material surface, thereby inhibiting subsequent biofilm formation. PDA can also serve as a fixed loading platform for metal ions, achieving Zn loading through coordination or adsorption. 2+ The continuous release of [something] enhances the antibacterial activity of the material.

[0102] The MIC and MBC test results of CuR@ZIF-8@PDA against E. coli are as follows: Figure 29 As shown, according to Figure 29 It can be seen that, after a two-fold serial dilution of the initial drug concentration of 2500.00 μg / mL and investigation of the antibacterial effect of CuR@ZIF-8@PDA on Escherichia coli in 96-well plates, the color of the wells in the fifth column of the 96-well plate changed from dark to light after resalicylate staining. This is because the living cells reduced the weakly fluorescent blue resalicylate to a strong pink fluorescence. Therefore, the color change from blue to pink in the wells reflects the strong growth activity of the bacteria. At a drug concentration of 2... 3At this point, the bacteria were inhibited, and the drug concentration was 312.50 μg / mL. Therefore, the MIC of CuR@ZIF-8@PDA against Escherichia coli was determined to be 312.50 μg / mL. To further verify its bactericidal effect, bacterial suspensions treated with different concentrations were plated on solid culture medium and cultured. The results are as follows. Figure 29 As shown in (b) of the diagram. According to Figure 29 As shown in (b), compared with the blank control group (0.00 μg / mL), the number of colonies on the plate gradually decreased with increasing drug concentration, indicating that CuR@ZIF-8@PDA has a significant concentration-dependent antibacterial / bactericidal effect on Escherichia coli. When the drug concentration was MIC, i.e., 312.50 μg / mL, only 2 colonies were observed on the plate, indicating that the material at the MIC concentration could significantly inhibit the growth and reproduction of most E. coli, but a very small number of bacteria still survived; when the drug concentration was further increased to 625.00 μg / mL, no obvious colony growth was observed on the plate, indicating that this concentration could completely kill E. coli in the culture system. Therefore, 625.00 μg / mL was determined to be the MBC of CuR@ZIF-8@PDA against E. coli.

[0103] ZIF-8@PDA cytotoxicity such as Figure 30 As shown. According to Figure 30 As shown in (a), under the conditions of ZIF-8@PDA concentration of 2 mg / mL, physiological saline as medium, and incubation in a constant temperature incubator at 37℃ for 1 h, the supernatant of the positive control group was obviously red, and the hemolysis rate was close to 100%, indicating that the red blood cells underwent complete hemolysis; the supernatant of the negative control group was clear and transparent, and the hemolysis rate was close to 0%, indicating that the red blood cell membrane structure remained intact. In contrast, the color of the supernatant of the ZIF-8@PDA group was similar to that of the negative control group, showing only slight hemolysis, and its hemolysis rate was 3.1%, which was lower than the safety threshold of 5%. This indicates that ZIF-8@PDA has good biocompatibility.

[0104] To further test the cytotoxicity of ZIF-8@PDA, this test case used the CCK-8 assay to detect its effect on the viability of mouse myoblasts (C2C12) and hepatocellular carcinoma cells (HepG2). The results are as follows: Figure 30 As shown in (b) of the diagram. According to Figure 30As shown in (b), the effect of ZIF-8@PDA on the viability of both C2C12 and HepG2 cells decreased with increasing concentration. When the ZIF-8@PDA concentration was between 10 and 20 μg / mL, the viability of both cell types remained above 90%. When the carrier concentration reached 160 μg / mL, the activity of ZIF-8@PDA on C2C12 cells was 76.51%, and on HepG2 cells it was 72.06%. This indicates that the carrier has good biocompatibility within the concentration range of 0–160 μg / mL. The slightly lower viability of HepG2 cells compared to C2C12 cells at most concentrations may be due to the PDA layer's ability to better control the Zn content in the ZIF-8 material under acidic conditions. 2+ Precipitation.

[0105] The survival rates of C2C12 cells and HepG2 cells under different concentrations of CuR, CuR@ZIF-8, and CuR@ZIF-8@PDA are as follows: Figure 31 As shown. According to Figure 31 As shown in (a), C2C12 cells maintained high cell viability even at lower concentrations after treatment with CuR@ZIF-8@PDA. At a concentration of 20 μg / mL, the survival rate of C2C12 cells was 76.45%, and at a concentration of 40 μg / mL, the cell viability remained at 65.94%. While the cell viability decreased by 4.45% compared to the CuR@ZIF-8 group, it still maintained relatively good cell viability. According to... Figure 31 Figure (b) shows the effect of different groups and concentrations of the drug on the activity of liver cancer cells. At a concentration of 5 μg / mL, CuR@ZIF-8@PDA did not inhibit the activity of liver cancer cells. With increasing concentration, CuR@ZIF-8@PDA showed the most significant inhibitory effect on HepG2 cell activity. At a concentration of 20 μg / mL, the cell viability was 57.84%, significantly lower than the 66.35% in the CuR group. This may be due to the synergistic effect of the drug and the carrier. At a concentration of 40 μg / mL, cell activity was below 50%, only 39.5%, indicating that CuR@ZIF-8@PDA had a good inhibitory effect on HepG2 cell activity at this concentration. The calculated IC50 of CuR@ZIF-8@PDA on HepG2 cells... 50 The concentration was approximately 29 μg / mL. CuR@ZIF-8@PDA showed better inhibitory effects on tumor cells than CuR@ZIF-8, possibly due to the more active pH response of the ZIF-8 material after PDA coating. During the PDA coating process, the main framework of the ZIF-8 material was effectively preserved, while the Zn content caused by the self-erosion at the ZIF-8-PDA interface was also reduced. 2+The release was regulated to a certain extent. The pH-dependent release characteristic exhibited by this system can promote drug release in an acidic microenvironment, thereby enhancing the inhibitory effect on HepG2 cells.

[0106] AO / EB ratios after treatment of HepG2 cells in each group are shown below. Figure 32 As shown, according to Figure 32 As can be seen, the AO / EB staining method was used to observe the cell viability of HepG2 cells after treatment with different materials. AO can enter the cell and bind to nucleic acids, emitting green fluorescence, while EB can enter cells with damaged cell membranes and emit red fluorescence. The control group showed predominantly green fluorescence, while the red fluorescence caused by EB was weaker, resulting in predominantly green fluorescence in the merged images. This is because the control group was not treated with drugs, had higher cell viability, and maintained intact cell membrane morphology. In the CuR group, the intensity of red fluorescence was enhanced, and the proportion of yellow and orange cells in the merged images increased, indicating that CuR can induce apoptosis in HepG2 cells and cause damage to the cell membrane structure. In the CuR@ZIF-8@PDA group, the red fluorescence was more obvious, the yellow and orange signals in the merged images were more enhanced, and the proportion of green signals further decreased. This indicates that this drug delivery system caused more significant cell damage to HepG2 cells, a result consistent with the previous cell viability experiment showing that "the drug delivery system has a stronger inhibitory effect on HepG2". This may be due to the synergistic effect of PDA in killing HepG2 cells.

[0107] This test case examined the changes in intracellular MDA and SOD levels in HepG2 cells after different samples were applied. The results are as follows: Figure 33 As shown. According to Figure 33 As shown in (a), the MDA content in the control group was 0.623 nmol / mg prot, while that in the ZIF-8@PDA group was 0.693 nmol / mg prot, slightly higher than the control group. The MDA content in the CuR group further increased to 0.936 nmol / mg prot, with the CuR@ZIF-8@PDA group having the highest MDA content at 1.403 nmol / mg prot. Figure 33As shown in (b), the changes in SOD activity and MDA content showed an opposite trend. The SOD level in the control group was 1.395 U / mg prot, while the SOD level in the ZIF-8@PDA group was slightly lower than that in the control group. The SOD level in the CuR group decreased significantly to 0.635 U / mg prot, and the SOD level in the CuR@ZIF-8@PDA group was the lowest, at only 0.45 U / mg prot. In summary, ZIF-8@PDA treatment alone had little effect on the redox status of HepG2 cells, while CuR treatment significantly increased the MDA content in HepG2 cells and inhibited SOD formation. This effect was more pronounced in the CuR@ZIF-8@PDA complex system. These results indicate that a drug delivery system constructed using curcumin as a model drug and ZIF-8@PDA as a carrier is more likely to lead to increased intracellular lipid peroxidation and decreased antioxidant defense capacity, resulting in more severe oxidative stress damage. This result is consistent with the trend of decreased cell viability and increased cell death observed in AO / EB staining mentioned earlier.

[0108] The DCFH-DA staining fluorescence image of HepG2 cells after CuR@ZIF-8@PDA treatment is shown below. Figure 34 As shown, according to Figure 34 It can be seen that the expression level of ROS in HepG2 cells was detected by the DCFH-DA probe after treatment with different drugs. After entering the cell, DCFH-DA is hydrolyzed by esterase to generate non-fluorescent DCFH, which is then oxidized to green fluorescent DCF under the action of ROS. Therefore, the intensity of green fluorescence in the cell can reflect the level of ROS expression. In the control group, only a weak green fluorescence signal can be observed under dark field conditions, indicating that the ROS expression level in the control group is low at this time.

[0109] The significantly increased green fluorescence intensity in the CuR group indicates that CuR can promote the production of ROS and induce oxidative stress in cells at a certain concentration. In contrast, the CuR@ZIF-8@PDA group showed the highest green fluorescence intensity and the widest green fluorescence coverage in the Merge plot, indicating more significant intracellular ROS accumulation. The stronger ROS signaling induced by CuR@ZIF-8@PDA may be related to the increased cellular uptake efficiency and effective intracellular release due to carrier delivery, thereby enhancing the interference with mitochondrial function and redox homeostasis and amplifying the oxidative stress effect. The ROS imaging results corroborate the aforementioned decrease in SOD and increase in MDA values, jointly demonstrating that CuR@ZIF-8@PDA can lead to a more pronounced oxidative stress response in HepG2 cells.

[0110] Overall, this invention employs polydopamine to coat ZIF-8 material, and the synthesized composite structure is characterized using SEM, XRD, XPS, and other testing methods. The results show that ZIF-8@PDA achieves PDA coating while retaining the original dodecahedral morphology of the ZIF-8 material.

[0111] Using curcumin as a model drug, a pH-responsive drug delivery system of CuR@ZIF-8@PDA was successfully constructed. Loading results showed that ZIF@PDA had the best loading effect on curcumin when the drug-to-carrier ratio was 2:1, with a loading rate of 51.72%. Release experiments showed that the CuR@ZIF-8@PDA drug delivery system had better pH responsiveness, which may be due to the increased permeability of PDA under acidic conditions.

[0112] In antibacterial experiments, CuR@ZIF-8@PDA showed good inhibitory effects against both Escherichia coli and Staphylococcus aureus. Its MIC for Staphylococcus aureus was 93.75 μg / mL and its MBC was 187.50 μg / mL, while its MIC for Escherichia coli was 312.50 μg / mL and its MBC was 625.00 μg / mL.

[0113] In vitro cell experiments showed that ZIF-8@PDA exhibited good biocompatibility with C2C12 cells and mammalian erythrocytes. CuR@ZIF-8@PDA showed excellent inhibitory effects on HepG2 cells, with cell viability reduced to only 39.5% at a concentration of 40 μg / mL. AO / EB staining experiments indicated that CuR@ZIF-8@PDA induced stronger apoptosis in HepG2 cells. MDA, SOD, and ROS assays showed that CuR@ZIF-8@PDA induced a more significant oxidative stress response compared to free CuR, and may further promote apoptosis.

[0114] In summary, the pH-based drug delivery system constructed using PDA as a modified material in this invention achieves acid-triggered controlled release while retaining the original structure of the ZIF-8 material, and enhances the inhibitory effect on liver cancer cells, Escherichia coli, and Staphylococcus aureus, providing a research basis for subsequent drug delivery and tumor targeted therapy.

[0115] In summary, this invention employs multiple characterization techniques, including X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and scanning electron microscopy (SEM), to systematically analyze the crystal structure, microstructure, and surface chemical composition of materials, establishing an intrinsic correspondence between structure, composition, and morphology. This provides a theoretical basis for subsequent research on drug loading, in vitro drug release behavior, and biological properties.

[0116] This invention also included drug loading and in vitro pH-responsive drug release performance tests: using curcumin as a model drug, it was loaded onto the drug delivery material using an impregnation method, and the drug loading was tested. Dynamic dialysis was used to simulate in vivo physiological conditions, and in vitro drug release experiments were conducted under physiological neutral conditions (pH 7.4) and tumor weakly acidic conditions (pH 5.0), respectively. The pH-responsive drug release characteristics of the drug delivery system were systematically tested to clarify the drug release patterns, advantages, and suitable application scenarios.

[0117] This invention also included biological performance testing: blood compatibility and cytotoxicity tests were conducted to systematically evaluate the biocompatibility and biological safety of the drug delivery material, laying a safe foundation for its in vivo application. Combining the antibacterial properties of curcumin, Gram-negative bacteria (Escherichia coli) and Gram-positive bacteria (Staphylococcus aureus) were used as model strains. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of the drug delivery system were determined using the two-fold dilution method to evaluate its in vitro antibacterial performance. Targeting the excellent antitumor activity of curcumin, in vitro cell experiments were conducted to explore the killing effect of the drug delivery system on HepG2 liver cancer cells and analyze its mechanism of action in inducing apoptosis.

[0118] The embodiments of the present invention have been described above. However, these embodiments are for illustrative purposes only and are not intended to limit the scope of the present invention. All other embodiments obtained by those skilled in the art based on the above embodiments of the present invention without inventive effort are within the protection scope of the present invention.

Claims

1. A ZIF-8 / PDA composite material, characterized in that, It includes ZIF-8 material and polydopamine coated on the surface of the ZIF-8 material.

2. The ZIF-8 / PDA composite material according to claim 1, characterized in that, The preparation method of the ZIF-8 material includes the following steps: mixing zinc nitrate and a portion of methanol to obtain a zinc salt solution, then mixing 2-methylimidazole and the remaining methanol to obtain a 2-methylimidazole solution, and then adding the 2-methylimidazole solution dropwise to the zinc salt solution while stirring and continuing to stir, followed by a coordination polymerization reaction; the mass ratio of zinc nitrate to a portion of methanol is 1.6:23~24; the mass ratio of zinc nitrate to 2-methylimidazole is 1.6:2.6~2.

7.

3. The ZIF-8 / PDA composite material according to claim 2, characterized in that, The coordination polymerization reaction is carried out at a temperature of 155-165 degrees Celsius for 17-19 hours.

4. A method for preparing a ZIF-8 / PDA composite material, characterized in that, The ZIF-8 / PDA composite material is the ZIF-8 / PDA composite material according to any one of claims 1 to 3, and includes the following steps: (1) Mix ZIF-8 material, methanol and water to obtain ZIF-8 dispersion; (2) The ZIF-8 dispersion is mixed with polydopamine and alkaline solution to react and obtain the ZIF-8 / PDA composite material.

5. The preparation method according to claim 4, characterized in that, In step (1), the mixing is ultrasonic mixing; The ultrasonic mixing power is 220~260 W, the frequency is 35~45 kHz, and the duration is 25~35 minutes.

6. The preparation method according to claim 4, characterized in that, The concentration of the alkaline solution is 0.08~0.11 mol / L; The mass-to-volume ratio of the ZIF-8 material to the alkaline solution is (290~310) mg: 3 mL.

7. The preparation method according to claim 4, characterized in that, The mass ratio of ZIF-8 material to polydopamine is 9~11:

1.

8. The preparation method according to claim 4, characterized in that, The reaction time is 2.8 to 3.2 hours.

9. An application of a ZIF-8 / PDA composite material in the field of drug delivery, characterized in that, The ZIF-8 / PDA composite material is the ZIF-8 / PDA composite material according to any one of claims 1 to 3.